FIGURE 9 in A revision of the subgenus Eurycercus (Eurycercus) Baird, 1843 emend. nov. (Cladocera: Eurycercidae) in the Holarctic with the description of a new species from Alaska - Bekker, Eugeniya I.; Kotov, Alexey A.; Taylor, Derek J. (Zenodo, 2012)
FIGURE 9. Eurycercus nipponica, limbs of parthenogenetic female from a swampy area (with a fresh bear trail in time of sampling) near Travianoy Cape, Kurilskoe Lake, Kamchatka Area, Russia A, limb I. B, inner distal lobe of limb I. C, limb II. D, its distal armature. E, limb III. F, distal armature of its gnathobase. G, limb IV. H, distal armature of its gnathobase. I, limb V. J, limb VI. Scale bar denotes 0.1 mm. : Published as part of Bekker, Eugeniya I., Kotov, Alexey A. & Taylor, Derek J., 2012, A revision of the subgenus Eurycercus (Eurycercus) Baird, 1843 emend. nov. (Cladocera: Eurycercidae) in the Holarctic with the description of a new species from Alaska, pp. 1-40 in Zootaxa 3206 (1) on page 27, DOI: 10.11646/zootaxa.3206.1.1, http://zenodo.org/record/5248211